Tinjauan Yuridis Pemutusan Kontrak Secara Sepihak oleh Bupati Nagekeo Terhadap Tenaga Harian Lepas (THL) di Kabupaten Nagekeo - Ana Maria Clarisa Dhiu Sawi; Agustinus Hedewata; Orpa Juliana Nubatonis (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2024)
The purpose of this research is to analyze the juridical review of unilateral contract termination by the regent of Nagekeo against casual daily workers in Nagekeo district. The type of research is Empirical Legal research, the type of data used in this research is qualitative descriptive data. The results of this study suggest that: (1) The reason for the Nagekeo Regent to unilaterally terminate the contract against the casual workers in Nagekeo Regency is to reduce the regional expenditure budget so that these funds can be allocated to build facilities for the people of Nagekeo Regency (2) The impact that occurred for casual workers at the time of contract termination was to cause a situation of lack of security and public order due to demonstrations against the dismissal of casual workers, reduced income for families who are members of casual workers, causing the economic wheels in the market to be quiet for some time and not optimal administrative services and public services for the community.